2023
DOI: 10.1186/s12961-022-00954-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards conceptualizing patients as partners in health systems: a systematic review and descriptive synthesis

Abstract: Background With the sharp increase in the involvement of patients (including family and informal caregivers) as active participants, collaborators, advisors and decision-makers in health systems, a new role has emerged: the patient partner. The role of patient partner differs from other forms of patient engagement in its longitudinal and bidirectional nature. This systematic review describes extant work on how patient partners are conceptualized and engaged in health systems. In doing so, it fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…This was particularly notable for forensic mental health patients with only two relevant papers published in 7 years out of the 675 originally retrieved papers (Abram et al, 2020;Tearle et al, 2020). Vanstone et al (2023) found 314 health research papers (published in peer reviewed journals between 2000 and 2021) where patients were cited as partners; of these 80 were research relating to mental health conditions. PPI in prison and particularly forensic mental health research appears behind general mental health in involving people with lived experience in research (Vanstone et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was particularly notable for forensic mental health patients with only two relevant papers published in 7 years out of the 675 originally retrieved papers (Abram et al, 2020;Tearle et al, 2020). Vanstone et al (2023) found 314 health research papers (published in peer reviewed journals between 2000 and 2021) where patients were cited as partners; of these 80 were research relating to mental health conditions. PPI in prison and particularly forensic mental health research appears behind general mental health in involving people with lived experience in research (Vanstone et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Vanstone et al. (2023) found 314 health research papers (published in peer reviewed journals between 2000 and 2021) where patients were cited as partners; of these 80 were research relating to mental health conditions. PPI in prison and particularly forensic mental health research appears behind general mental health in involving people with lived experience in research (Vanstone et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations